Updated measurement of decay-time-dependent CP asymmetries in D0→K+K− and D0→π+π− decays; Physical Review D; Vol. 101, iss. 1 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen